Study on different finite difference methods at skin interface for burn prediction in protective clothing evaluation - Zhai, L.; Camenzind, M.; Li, J.; Rossi, R. M. (Fire and materials, 2017)
Summary For protective clothing evaluation by using the flame engulfment method, a skin burn injury model is required to predict burn degree of the covered skin. By applying finite difference methods, 2 numerical methods are compared. One is based on equivalent heat intensity; the other is based on the law of conservation of energy. In this study, skin temperature rise is compared between these 2 methods by using homogeneous skin properties as well as the analytical solutions. Differences between these 2 methods in application of measured heat exposure tests data are also explored. The results show that assuming equivalent heat intensity at the skin layer interfaces overestimates severity of burn injury. Burn injury time is sensitive to the investigated numerical methods, especially for third‐degree burns. The differences of the 2 methods can be reduced by optimization of the grid size using the test cases described in ASTM F1930. A detailed description of requirements regarding applicable numerical methods in future revisions of the relevant standards is recommended. The finite difference model applied in this paper can act as an effective tool to predict temperature distribution in the skin as well as predict burn injury for evaluation of thermal protective clothing.